2013
DOI: 10.4067/s0718-58392013000200001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated air temperature on physiological characteristics of flag leaves and grain yield in rice

Abstract: 1As an indispensable environment element for crop growth, air temperature has brought challenge for the sustainable development of rice (Oryza sativa L.) production. Elevated air temperature led to great loss in rice grain yield in many districts suffering from heat stress due to the greenhouse effect worldwide, which has received more and more attention from researchers. A field experiment was conducted to investigate impacts of high air temperature (HAT) after rice heading stage on dynamics of SPAD values, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
2
17
1
Order By: Relevance
“…The MDA concentration was higher in 'F60' plants at 40 °C, as was the percentage of electrolyte leakage, indicating greater cell membrane damage. Similar results were observed in rice plants by Zhang et al (2009) and Liu et al (2013), who also reported that the highest values of MDA occurred in the leaves of rice cultivars with enhanced susceptibility to heat stress.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The MDA concentration was higher in 'F60' plants at 40 °C, as was the percentage of electrolyte leakage, indicating greater cell membrane damage. Similar results were observed in rice plants by Zhang et al (2009) and Liu et al (2013), who also reported that the highest values of MDA occurred in the leaves of rice cultivars with enhanced susceptibility to heat stress.…”
Section: Discussionsupporting
confidence: 73%
“…Challenging temperature conditions of 37 °C/30 °C (day/ night) increase the electrolyte leakage percentage and MDA content in rice (Zhang et al, 2009). Similar results were also obtained by Liu et al (2013) in rice plants.…”
Section: Introductionsupporting
confidence: 76%
“…A change in concentration of MDA is a good indicator of membrane structural integrity under temperature stress (Sanchez-Reinoso et al 2014). Increase temperature stress 37 C/30 C (day/night) increased MDA content and electro leakage percentage in rice (Zhang et al 2009;Liu et al 2013).…”
Section: Physiological and Biochemical Heat Stress Indicators In Ricementioning
confidence: 99%
“…It has been established that rice is most sensitive to high temperature stress during reproductive stage, that is, from panicle initiation to grain‐filling stage (Jagadish, Craufurd, & Wheeler, ; Jagadish et al., ; Prasad, Boote, Allen, Sheehy, & Thomas, ). High temperature during reproduction stage induces decreased soluble sugar and protein, chlorophyll content and photosynthetic production in rice leaves (Liu, Wu, Li, Ma, & Zhou, ). These physiological changes inevitably result in insufficient assimilates supply from leaves and stems to grains, retarding the normal growth of grain and eventually reducing grain weight (Kobata & Uemuki, ; Shi et al., ).…”
Section: Introductionmentioning
confidence: 99%